Hazardous Effects of Arsenic Contaminated Water on the Biological Characteristics of Fishes: A Review - Kanwal, Maimoona; Hussain, Mubashar; Younus, Waqar (BioScientific Review, 2019)
The aim of the current review is to deliberate on arsenic chemistry, its existence in aquatic ecosystem and its effects on the biological systems of fishes which are regarded as potential indicators for any change in water quality. Water is a major storehouse of arsenic which is present in the form of arsenate and arsenite. Anthropogenic activities including unlimited application of arsenic pesticides, industrial activities and mining operations have increased the universal incidence of soluble arsenic above tolerable levels of 0.010 mg/L. Variations in fish behaviour, growth rate, haematological and biological parameters and organ systems have been observed in arsenic contaminated water. Data regarding these parameters indicate that the fish shows aggressive behaviour and its weight increases due to a high arsenic uptake. The production rate of biochemical compounds like carbohydrates, proteins and lipids is reduced due to arsenic bonding with their precursors. Among organ systems, skin is a highly affected organ, while muscles are the least affected due to high arsenic concentration. Low concentration of arsenic results in bioaccumulation, conspicuously in liver and kidney, upon incessant exposure to freshwater ﬁsh. This bioaccumulation turns into biomagnification and becomes the cause of lethal diseases in human beings, such as hyperglycaemia, diminution of enzymatic activities and immune system abnormalities. Keeping in view all of these above mentioned facts, it is imperative to take action against excessive arsenic usage and to develop its eco-friendly management ways.